Durability and underlying physiological factors: How do they change throughout a cycling season in semiprofessional cyclists? - Voet, J. G.; Lamberts, R. P.; Viribay, A.; de Koning, J. J.; van Erp, T. (International Journal of Sports Physiology and Performance, 2024)
Purpose To investigate how cycling time-trial (TT) performance changes over a cycling season, both in a "fresh" state and in a "fatigued" state (durability). Additionally, the aim was to explore whether these changes are related to changes in underlying physiological factors such as gross efficiency, energy expenditure (EE), and substrate oxidation (fat oxidation [FatOx] and carbohydrate oxidation [CarbOx]).